Highly expressed CENPL is correlated with breast cancer cell proliferation and immune infiltration - Gui, Zhengwei; Tian, Yao; Liu, Shiyang; Yu, Tianyao; Liu, Chenguang; Zhang, Lin (Frontiers in Oncology, 2023)
Abstract Background： Centromere protein L (CENPL) is associated with a variety of human diseases. However, its function in breast cancer remains uncertain. Methods: The Cancer Genome Atlas (TCGA) and genotype-tissue expression across cancer data were used to investigate CENPL expression. Using TCGA clinical survival data, the relationship between CENPL expression and patient prognosis was assessed. Using the cluster profiler R software tool, enrichment analysis of CENPL was carried out. Additionally, by studying the TCGA database, the relationship between CENPL expression and immune cell infiltration was assessed. To evaluate CENPL's impact on breast cancer cell proliferation, the CCK8 test and colony-formation assay were carried out. Scratch testing and the transwell assay were used to evaluate the effects of CENPL on breast cancer cell migration. Results: Breast cancer was one of numerous tumor forms with high CENPL expression. Significant relationships between high CENPL expression and the cell cycle, nuclear division, organelle fission, and chromosome segregation were found. Further investigation revealed that minimal infiltration of CD8-positive T cells and natural killer (NK) cells and high levels of Tregs and macrophages were correlated with high levels of CENPL expression. CENPL expression was linked to more than half of the ICP genes. Breast cancer cells' ability to proliferate and migrate was decreased by CENPL knockdown. Conclusions: Our findings suggest that CENPL may be an oncogene in breast cancer and a predictor of efficacy of immunotherapy for breast cancer.